1976
DOI: 10.1128/iai.14.5.1213-1220.1976
|View full text |Cite
|
Sign up to set email alerts
|

Blastogenic response of human lymphocytes to oral bacterial antigens: comparison of individuals with periodontal disease to normal and edentulous subjects

Abstract: Cell-mediated immunity in humans to antigens derived from oral plaque bacteria was investigated by using the lymphocyte blastogenesis assay. Subjects with varying severities of periodontal disease including normal, gingivitis, periodontitis, and edentulous were compared. Mononuclear leukocytes were separated from peripheral blood and cultured with antigens prepared by sonication of Actinomyces viscosus (AV), Actinomyces naeslundii (AN), Veillonella alcalescens (VA), Leptotrichia buccalis (LB), Bacteroides mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
2

Year Published

1978
1978
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(55 citation statements)
references
References 18 publications
5
48
2
Order By: Relevance
“…Among bacterial products reported to act as B-cell activators in RA are bacterial peptidoglycans (Pardo et al 1984). Increased blast responses and polyclonal B-cell activation to extracts of dental plaque were observed in several studies of peripheral lymphocytes from patients with periodontitis (Patters 1976, Smith et al 1979, Bick et al 1981, Donaldson et al 1982, Osterberg et al 1983.…”
Section: Discussionmentioning
confidence: 93%
“…Among bacterial products reported to act as B-cell activators in RA are bacterial peptidoglycans (Pardo et al 1984). Increased blast responses and polyclonal B-cell activation to extracts of dental plaque were observed in several studies of peripheral lymphocytes from patients with periodontitis (Patters 1976, Smith et al 1979, Bick et al 1981, Donaldson et al 1982, Osterberg et al 1983.…”
Section: Discussionmentioning
confidence: 93%
“…Numerous studies utilizing lymphocyte transformation tests have tried to determine the role of cell-medialed immunity in the developmcnl and maintenance of chronic periodontal disease. There is a great deal of evidence that extracts of isolated plaque bacteria or pooled plaque stimulate peripheral blood lymphocytes to blastogenesis in vitro, and this response 56T correlated with the gingival and periodontal inflammatory response (Ivanyi & Lehner 1970, Horton, Oppenheim & Mergenhagen 1974, Patters et al 1976, Lang & Smith 1977, Smith, Lang & Loe 1978. However, some other investigators refute such an association (Kiger.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, attempts have been made, using peripheral blood lymphocyte responses to specific plaque bacterial antigens, to elucidate the role played by these organisms in the pathogenesis of chronic inflammatory periodontal disease (Baker et al 1976, Patters et al 1976). found that the in vitro response to A. viscosus and A. naestundii correlated more highly to plaque and gingivitis scores, while that of B. melaninogenicus related more to pocket depths and loss of attachment.…”
Section: Ivanyimentioning
confidence: 99%